The Borders of the Netherworld in Ugaritic Thought - Thompson, Shane M. (Antiguo Oriente, 2024)
This paper explores the textual evidence for the borders of the Ugaritic Netherworld, arguing that the Netherworld borders are reflective of the actual “real-world” borders of Ugarit. Following this discussion, the question is raised as to whether these Netherworld borders are traversable like borders in the world of the living. Using comparative textual and archaeological evidence, the paper postulates that the borders of the Netherworld may have indeed been envisioned as borders which the deceased were able to cross, just like the borders between the land of the dead and the land of the living. While three of Ugarit’s borders are characterized by mountainous topography, the fourth border is the Mediterranean Sea. Including the evidence of anchors in burial contexts alongside a discussion of Ugarit’s real-world and Netherworld borders allows for the possibility that these anchors were used by the deceased in the Netherworld as they continued to sail on the sea.